2020
DOI: 10.1039/c9ta12827a
|View full text |Cite
|
Sign up to set email alerts
|

The influence of interfacial interactions on the conductivity and phase behaviour of organic ionic plastic crystal/polymer nanoparticle composite electrolytes

Abstract: The interactions between OIPCs and polymer nanoparticles create interfacial layers that control the ion mobility of the resulting composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 36 publications
5
43
0
Order By: Relevance
“…The addition of OIPC to a conducting polymer has been studied, providing promising results with an enhancement of ×9 for electronic conductivity (17.7 S cm –1 ) and ×180 for ionic conductivity in the 40/60 PEDOT–Cl/[C 2 mpyr]­[FSI] composite. Surprisingly, ionic conductivity values of around 10 –4 S cm –1 at room temperature were obtained, which might be due to the formation of highly conducting pathways through the interphase of PEDOT–Cl and [C 2 mpyr]­[FSI], as has been suggested for OIPC/PVdF composites. , It is important to note that these ionic conductivity values are really close to the desirable range of solid electrolytes (∼10 –3 S cm –1 ) in the field of ESSs . Furthermore, the activation energy for conduction in these composites was very low, as observed in the Arrhenius representation of ionic conductivity versus inverse temperature (Figure S3).…”
Section: Discussionmentioning
confidence: 74%
“…The addition of OIPC to a conducting polymer has been studied, providing promising results with an enhancement of ×9 for electronic conductivity (17.7 S cm –1 ) and ×180 for ionic conductivity in the 40/60 PEDOT–Cl/[C 2 mpyr]­[FSI] composite. Surprisingly, ionic conductivity values of around 10 –4 S cm –1 at room temperature were obtained, which might be due to the formation of highly conducting pathways through the interphase of PEDOT–Cl and [C 2 mpyr]­[FSI], as has been suggested for OIPC/PVdF composites. , It is important to note that these ionic conductivity values are really close to the desirable range of solid electrolytes (∼10 –3 S cm –1 ) in the field of ESSs . Furthermore, the activation energy for conduction in these composites was very low, as observed in the Arrhenius representation of ionic conductivity versus inverse temperature (Figure S3).…”
Section: Discussionmentioning
confidence: 74%
“…The materials can possess plastic behavior and high ionic conductivities. In previous works, Nti et al [ 25 ] recently reported their study on the interactions between OIPCs and polymers, such as poly(vinylidene fluoride) (PVDF) and polystyrene (PS), which showed that the combination of OIPCs and polymer particles enhanced the ionic conductivity and resulted in good mechanical stability of the composites. Therefore, in this article the potential of organic ionic plastic crystals to enhance both the ionic conductivity and the mechanical properties of the PEDOT:PolyDADMA OMIECs was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table S1, the peak wavenumbers for the spectra of the interlayer and [C 2 mpyr][FSI] composite are almost the same as those of [C 2 mpyr][FSI]. In contrast to the FTIR spectrum of the composite composed of PVdF nanoparticles and [C 2 mpyr][FSI], [25] no obvious peak shifts are observed for the spectrum of the interlayer. This is due to the low weight ratio of PVdF (10 wt %) in the interlayer.…”
Section: Resultsmentioning
confidence: 76%
“…To further analyze SEI formation at the first charging, FTIR spectroscopy was performed for the surfaces of the solid-state graphite-[C 2 mpyr][FSI] composite anodes (70 wt % graphite anode + 30 wt % [C 2 mpyr][FSI] composite). Figure 1c [25] no obvious peak shifts are observed for the spectrum of the interlayer. This is due to the low weight ratio of PVdF (10 wt %) in the interlayer.…”
Section: Initial Charge-discharge Profilementioning
confidence: 99%